The Roles of Artificial Intelligence Technology in Enhancing Remote Education for University Students in Chongqing, China - Shasha , Peng; Hussin , Norehan Binti; Suryani, Ina (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This study investigates the roles of Artificial Intelligence (AI) in enhancing remote education for university students in Chongqing, China, focusing on the post-COVID-19 era. Employing a Systematic Literature Review (SLR), the research addresses two key questions: (RQ1) the reasons for using AI in remote education, and (RQ2) the challenges associated with its implementation. A search was conducted using Google Scholar, selected for its broad access to interdisciplinary scholarly works. Articles published between 2021 and 2024 were analyzed. The study found that AI enhances remote education by offering convenience and flexibility tailored to students’ individual learning paces and needs. It enriches the learning experience through diverse and engaging course content and enables personalized learning paths with resource recommendations based on students’ abilities and learning history. Key tools include virtual tutoring systems, intelligent assignment grading systems, and virtual laboratories, which collectively address educational gaps in remote settings. However, challenges persist, including technical adaptation issues, data privacy and security concerns, unreliable network connections, and a lack of interpersonal interaction. The paper concludes with improvement measures such as strengthening data security, improving infrastructure, and incorporating hybrid learning approaches. Kajian ini menyelidiki peranan Kecerdasan Buatan (AI) dalam meningkatkan pendidikan jarak jauh untuk pelajar universiti di Chongqing, China, dengan fokus pada era pasca-COVID-19. Menggunakan Kajian Literatur Sistematik (SLR), penyelidikan ini menangani dua soalan utama: (RQ1) sebab-sebab penggunaan AI dalam pendidikan jarak jauh, dan (RQ2) cabaran yang berkaitan dengan pelaksanaannya. Pencarian dilakukan menggunakan Google Scholar, yang dipilih kerana akses luasnya kepada karya akademik pelbagai disiplin. Artikel yang diterbitkan antara tahun 2021 hingga 2024 dianalisis. Kajian mendapati bahawa AI meningkatkan pendidikan jarak jauh dengan menawarkan kemudahan dan fleksibiliti yang disesuaikan dengan kadar dan keperluan pembelajaran individu pelajar. AI memperkayakan pengalaman pembelajaran melalui kandungan kursus yang pelbagai dan interaktif serta membolehkan laluan pembelajaran yang diperibadikan dengan cadangan sumber berdasarkan keupayaan dan sejarah pembelajaran pelajar. Alat utama termasuk sistem tunjuk ajar maya, sistem pemarkahan tugasan pintar, dan makmal maya, yang secara kolektif menangani kekurangan pendidikan dalam suasana jarak jauh. Namun, cabaran tetap ada, termasuk isu penyesuaian teknikal, kebimbangan mengenai privasi dan keselamatan data, sambungan rangkaian yang tidak stabil, dan kekurangan interaksi interpersonal. Kajian ini diakhiri dengan langkah-langkah penambahbaikan seperti memperkukuh keselamatan data, meningkatkan infrastruktur, dan menggabungkan pendekatan pembelajaran hibrid.